Comparison of components profile in herbal raw material, extract and pharmaceuticals of Hedera Helix - Ivan Bezruk (ScienceRise: Pharmaceutical Science, 2020)
The aim. To investigate both the profile of components and possible difference among herbal raw materials, semi-products and pharmaceuticals of Hedera helix for determination of main standartisation markers.